Brand Attitude, Brand Experience, Brand Love and Word of Mouth: Evidence from China and Malaysia's IKEA - Elanchelian, Pavitra A/P; Pang, Ziyi; Pu, Yunfei; Raja Ahmad Zulfakar, Raja Nur Zakirah Binti (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
IKEA is a fast-growing multinational home furnishings company started in 1943 in Sweden. Using a comparative analysis of the IKEA brand in Malaysia and China, this research intends to analyze the relationship between brand attitude, brand experience, brand love, and word of mouth. The data collected from China (N=100) and Malaysia (N=100) revealed that brand attitude, brand experience, and brand love impact word of mouth. This paper contributes to the fast-growing consumer-brand relationships literature by exploring the role of brand attitude, brand experience, and brand love in retail brands in China and Malaysia. It also intends to understand better how to build and nurture effective brand attitude, brand experience, and brand love to elicit intense and passionate feelings towards retail brands. Keywords: Brand Attitude, Brand Experience, Brand Love, China, IKEA, Malaysia, Word of Mouth